Paper Bastions: Architecting Academic Citadels from 1991 to 2009 - Walsh, Stephen; Yan, Jie; Mangematin, Vincent; Mei, Maggie (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2017)
How were paper bastions added to the walls of academic citadels? By mapping the evolution of the coauthorship network in 180 management journals from 1991 to 2009, we identify an elite league of business schools that retained dominance despite the research community’s significant growth. The elite universities maintain their prominence through a loop of reinforcement involving the peer review process and third-party ranking bodies, though the perceived quality of the papers published was declining as measured by the percentage of overall citations. Leading U.S. universities dominate top journal publications, while new local poles of management research among European and Asian universiteis emerged.